“Executive Compensation-Firm Performance relationship: A perspective from India” - Chandani, Arti; Mehta, Mita; Sarvaiya, Harsha (International Journal of Psychosocial Rehabilitation, 2020)
The Indian Companies Act, 2013 under section 197 contains provision towards maximum managerial remuneration. The total remuneration to directors and managers should not exceed 11% of its net profit for the financial year. There are other provisions relating to the payment of remuneration which act as the measures to control any abnormal behaviour of management towards payment of remuneration. There are firms, headed by CEO, who were paid too much at the expense of the stakeholders, which also manifests executives’ self-interest with complete lack of accountability for stakeholders and a gloomy picture of corporate governance. This study aims to examine the relationship between executive compensation and firm performance of BSE 200 listed firms in India. There has been research in this area in the countries such as US, UK and other countries, however little literature is available in emerging economies especially in the India. The amount of literature of executive pay and firm performance, which is available for Indian companies, is very limited. There is dearth of recent literature on executive pay and firm performance with recent data. Also, we could not find a study or research where executive compensation and pay performance, market based and accounting based, has been studied. Therefore, this study finds a unique place in the existing literature. Present study is based on the executive compensation for the year 2017 where data has been collected from Bloomberg and Prowess. Size of the firm is a significant variable in explaining executive compensation. Firm’s performance is a major factor affecting executive compensation. The pay performance relationship does not hold true in the case of small firms in the sample. Firms’ performance, market based and accounting based, is negatively correlated with executive compensation.